2011
DOI: 10.1590/s1807-59322011000700022
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil preserves diastolic relaxation after reduction by L-NAME and increases phosphodiesterase-5 in the intercalated discs of cardiac myocytes and arterioles

Abstract: OBJECTIVES:We investigated the influence of sildenafil on cardiac contractility and diastolic relaxation and examined the distribution of phosphodiesterase-5 in the hearts of hypertensive rats that were treated with by NG-nitro-L-arginine methyl ester (L-NAME).METHODS:Male Wistar rats were treated with L-NAME and/or sildenafil for eight weeks. The Langendorff method was used to examine the effects of sildenafil on cardiac contractility and diastolic relaxation. The presence and location of phosphodiesterase-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Earlier studies have shown that the effects of the acute, short-term and chronic inhibition of phosphodiesterase-5A (PDE5A) inhibitors on the cardiovascular system in healthy or patients with non-failing hearts were small and not likely to be clinically significant (Jackson et al 1999;Manfroi et al 2003 andRicardi et al 2010). However, in failing or chronically loaded hearts, the chronic inhibition significantly improved the myocardial dysfunction and LV end diastolic pressure and stiffness with inhibition of myocardial remodeling (Takimoto et al 2005;Nagayama et al 2009;Ferreira-Melo et al 2011 andWestermann et al 2012). This finding could be explained by increased PDE5A-dependent cGMP-esterase activity in failed hearts, thereby amplifying the cGMP-dependent signaling resulting in much larger changes in PKG-1 activation after PDE5A inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that the effects of the acute, short-term and chronic inhibition of phosphodiesterase-5A (PDE5A) inhibitors on the cardiovascular system in healthy or patients with non-failing hearts were small and not likely to be clinically significant (Jackson et al 1999;Manfroi et al 2003 andRicardi et al 2010). However, in failing or chronically loaded hearts, the chronic inhibition significantly improved the myocardial dysfunction and LV end diastolic pressure and stiffness with inhibition of myocardial remodeling (Takimoto et al 2005;Nagayama et al 2009;Ferreira-Melo et al 2011 andWestermann et al 2012). This finding could be explained by increased PDE5A-dependent cGMP-esterase activity in failed hearts, thereby amplifying the cGMP-dependent signaling resulting in much larger changes in PKG-1 activation after PDE5A inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In translational medicine, the drug discovery or new potential uses for currently available drugs seem to be an interesting approach for the treatment of RH. Sildenafil administration in hypertensive rats induced by NG‐nitro‐L‐arginine methyl ester (L‐NAME), reduced left ventricular diastolic dysfunction in comparison with untreated hypertensive rats . In addition, sildenafil demonstrated a protective effect in the cardiomyopathy induced by L‐NAME associated with reduction of cardiac remodeling and increased cyclic guanosine monophosphate (cGMP) levels in treated rats …”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil administration in hypertensive rats induced by NG-nitro-L-arginine methyl ester (L-NAME), reduced left ventricular diastolic dysfunction in comparison with untreated hypertensive rats. 21 In addition, sildenafil demonstrated a protective effect in the cardiomyopathy induced by L-NAME associated with reduction of cardiac remodeling and increased cyclic guanosine monophosphate (cGMP) levels in treated rats. 22 In the clinical setting, a recent study has suggested that acute intake of sildenafil improves (1) hemodynamic parameters-reducing mean BP levels by reducing total peripheral resistance (TPR)-and (2) diastolic function in patients with RH.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, this effect was reversed by oral administration of sildenafil, a selective phosphodiesterase type 5 inhibitor (IPDE-5) after 8 weeks of treatment 8 . Indeed, immunohistochemistry revealed reduced L-NAME-related myocardial lesions, in addition to increased PDE-5 intensity in the intercalary discs between myocytes 9 . Hence, this finding was related to improvement in LVDD due to direct sildenafil effect on cardiac relaxation in L-NAME-treated rats.…”
Section: Introductionmentioning
confidence: 96%